2020
DOI: 10.3390/pathogens9060424
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Foot-and-Mouth Disease Virus in Swine Meat Juice

Abstract: Foot-and-mouth disease virus (FMDV) is a highly contagious agent that impacts livestock industries worldwide, leading to significant financial loss. Its impact can be avoided or minimized if the virus is detected early. FMDV detection relies on vesicular fluid, epithelial tags, swabs, serum, and other sample types from live animals. These samples might not always be available, necessitating the use of alternative sample types. Meat juice (MJ), collected after freeze-thaw cycles of skeletal muscle, is a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…All negative samples were defined as such by no amplification produced when tested by the FMDV 3D pan-serotype rRT-PCR but also the presence of a quality template by producing a Cq ≤ 35.99 on the Xeno rRT-PCR assay. Eighteen remnant clinical samples ( 42 ) and two mock viral infections were evaluated. These samples included five tissue sample homogenates (porcine lymph node, porcine tongue and three bovine tongue tissues from different animals), five porcine serum samples, four porcine oral swab samples, four porcine oral fluid samples and BHK-21 cell culture supernatant collected from PBS mock viral infections collected two and three DPI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All negative samples were defined as such by no amplification produced when tested by the FMDV 3D pan-serotype rRT-PCR but also the presence of a quality template by producing a Cq ≤ 35.99 on the Xeno rRT-PCR assay. Eighteen remnant clinical samples ( 42 ) and two mock viral infections were evaluated. These samples included five tissue sample homogenates (porcine lymph node, porcine tongue and three bovine tongue tissues from different animals), five porcine serum samples, four porcine oral swab samples, four porcine oral fluid samples and BHK-21 cell culture supernatant collected from PBS mock viral infections collected two and three DPI.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the SAT1, SAT3 and SAT2 topotype VII rRT-PCR assay diagnostic specificity was performed using samples that were confirmed to be true negatives by the FMDV 3D pan-serotype rRT-PCR. The samples were remnant negative samples obtained from previous animal experiments conducted in the laboratory ( 42 ). The samples included five tissue sample homogenates (porcine lymph node, porcine tongue and three bovine tongue tissues from different animals), five porcine serum samples, four porcine oral fluids samples, four porcine oral fluid samples and BHK-21 cell culture supernatant collected from PBS mock viral infections collected two and three DPI.…”
Section: Methodsmentioning
confidence: 99%
“…The sample content determination does not need to open the reaction tube, and can be analyzed by the fluorescence signal intensity generated during the qRT-PCR amplification process, avoiding cross-contamination between samples ( Galluzzi et al, 2018 ). qRT-PCR has the advantages of rapidity and sensitivity, and is suitable for different clinical sample types including swabs, sera, vesicular fluid, milk and tissue samples ( Burkhalter and Savage, 2017 ; Fontel et al, 2019 ; Yeo et al, 2020 ; Armson et al, 2020a ). At present, Real-Time PCR is a commonly used method to detect the pathogens of animal diseases.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Armson et al determined the utility of testing pooled milk by rRT-PCR as an alternative approach for FMD surveillance, and proved that pooled milk has potential value as a surveillance sample to reveal subclinical FMD infection ( Armson et al, 2020a , b ). Yeo et al amplified the FMDV genomic sequence in meat juice using qRT-PCR and confirmed the presence of FMDV RNA ( Yeo et al, 2020 ). The discovery indicated that meat juice can be used as a good sample type for FMDV detection and play a role in the import and export quarantine of meat products ( Yeo et al, 2020 ).…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…The potential use of meat exudate for the detection of transboundary and endemic diseases has been explored previously. Genomic RNA of classical swine fever virus (CSFV) and foot and mouth disease virus (FMDV) have been successfully detected in meat exudate [ 34 , 35 , 36 ]. Meat exudate has also been used successfully employed for antibody-based serosurveillance of several other viral (influenza A virus, porcine circovirus 2, Aujeszky’s disease, porcine epidemic diarrhea virus, porcine reproductive and respiratory syndrome virus), bacterial ( Salmonella spp., Mycoplasma hyopneumoniae , and Yersinia enterocolitica ), and protozoal ( Trichinella spp.…”
Section: Introductionmentioning
confidence: 99%